2016
DOI: 10.1299/mej.16-00120
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave modulation due to discharged plasma using a shock tube

Abstract: The interaction phenomenon between shock waves and the DC-discharged plasma was experimentally investigated to aid future supersonic aerodynamic performance improvements. A shock tube was used to generate the shock wave. For the discharged plasma generation, a wedge type test model with electrodes (anode and cathode) connected to the power supply system was installed into the shock tube measurement section. The nominal shock wave Mach number in the experiment was 2.0. The plasma input power range was from 0 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This effect can be used to attenuate the negative impact of the shock wave on the environment when designing supersonic aircraft. When studying the interaction of a nonequilibrium plasma medium (gas-discharge plasma of volume and surface discharges) with shock waves (Mach numbers from 2 to 7), the effect of broadening the shock wave and splitting it into several gas-dynamic discontinuities was detected by shadow imaging [2][3]. It was theoretically shown that with the aid of fast local (t < 1 μs) heating of the flow, the shock wave can be destroyed if the threshold energy input for a given shock wave intensity and flow parameters is exceeded [4].…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be used to attenuate the negative impact of the shock wave on the environment when designing supersonic aircraft. When studying the interaction of a nonequilibrium plasma medium (gas-discharge plasma of volume and surface discharges) with shock waves (Mach numbers from 2 to 7), the effect of broadening the shock wave and splitting it into several gas-dynamic discontinuities was detected by shadow imaging [2][3]. It was theoretically shown that with the aid of fast local (t < 1 μs) heating of the flow, the shock wave can be destroyed if the threshold energy input for a given shock wave intensity and flow parameters is exceeded [4].…”
Section: Introductionmentioning
confidence: 99%